TINJAUAN SOSIO-YURIDIS TERHADAP “PAK OGAH” DI DAERAH KOTA MAKASSAR - Umar, Firman; Nurfaathirany, Ririn; Sjarif, dila (Jurnal Tomalebbi, 2024)
Socio-juridical Review of Mr. Ogahin Makassar City Area. Thesis Faculty of Social Sciences and Law, Study ProgramPancasila and Citizenship Education Study Program. Supervised by Firman Umar and Ririn Nurfaathirany.Research This study aims to determine 1) the position of Pak Ogah in the Makassar City Regional Regulation,2) Supervision and Handling System of Mr. Ogah in Makassar City, 3) sanctions for Mr. Ogah's activities in Makassar City.pak ogah who are active in Makassar city.Approach qualitative approach is descriptive research and tends to use inductive method analysis.tends to use analysis with the inductive method. The results of this study indicate that The existence of Mr. Ogah is still reaping pros and cons as a result of the absence of a clear traffic management system from the authorities. clear traffic management system from the authorities. they remain illegal and cannot be legally illegal and cannot be said to be legitimate. The position of Mr. Ogah in the government is regulated in the Makassar City Regional Regulation No. 7 of 2021 concerning public order, tranquility, and protection of the community. a person then chooses Mr. Ogah as an alternative profession because of related to economic factors or poverty, low education level, inadequate work experience. low level of education, inadequate work experience. Monitoring and handling system carried out by stakeholders in accordance with the governing regulations. Threat of sanctions for pak ogah who continue their activities are regulated in article 41 paragraph (2) and (3) Makassar City Regional Regulation on Peace, Order and Community Protection.